How are hospitals in England caring for women at risk of preterm birth in 2021? The influence of national guidance on preterm birth care in England: a national questionnaire - Naomi Carlisle; Angharad Care; Dilly O. C. Anumba; Sonia Dalkin; Jane Sandall; Andrew H. Shennan (BMC, 2023)
Abstract Background National guidance (Saving Babies Lives Care Bundle Version 2 (SBLCBv2) Element 5) was published in 2019, with the aim to standardise preterm care in England. We plan to identify how many preterm birth surveillance clinics there are in England, and to define current national management in caring for women who are both asymptomatic and high-risk of preterm birth, and who arrive symptomatically in threatened preterm labour, to assist preterm management both nationally and internationally. Methods An online survey comprising of 27 questions was sent to all maternity units in England between February 2021 to July 2021. Results Data was obtained from 96 units. Quantitative analysis and free text analysis was then undertaken. We identified 78 preterm birth surveillance clinics in England, an increase from 30 preterm clinics in 2017. This is a staggering 160% increase in 4 years. SBLCBv2 has had a considerable impact in increasing preterm birth surveillance clinic services, with the majority (61%) of sites reporting that the NHS England publication influenced their unit in setting up their clinic. Variations exist at every step of the preterm pathway, such as deciding which risk factors warrant referral, distinguishing within particular risk factors, and offering screening tests and treatment options. Conclusions While variations in care still do persist, hospitals have done well to increase preterm surveillance clinics, under the difficult circumstances of the COVID pandemic and many without specific additional funding.